The complete chloroplast genome of Phlegmariurus phlegmaria, one representative species of genus Phlegmariurus - Tang, Li-Ming (Mitochondrial DNA B Resour, 2020)
Phlegmariurus (Herter) Holub is the largest genus of Lycopodiaceae, with about 250 species distributed in the tropics and subtropics of the world. Phlegmariurus phlegmaria is the representative species of Phlegmariurus. In this study, we reported the complete chloroplast genome of P. phlegmaria. This complete chloroplast genome is 1,49,711 bp in size. In total, 134 genes were identified, including 84 protein-coding genes, 42 tRNA genes, and eight rRNA genes. In phylogenetic analysis, a close relationship with genus Huperzia was supported by maximum-likelihood (ML) tree. The complete plastome of P. phlegmaria will provide potential genetic resources to understand the evolution of lycophytes.